Contraintes socioculturelles de la-non déclaration des naissances chez les communautés peulhs dans le Département de Korhogo (Côte d’Ivoire) (International Journal of Scientific Research and Management (IJSRM), 2021)
Despite the ratification of international laws on the rights of peoples as well as those that regulate the functioning of civil status in Côte d’Ivoire, the issue of birth registration is an acute one in certain communities, particularly among the Peulhs living in the Department of Korhogo. The aim of this purely qualitative study is to understand the social logic behind the non-declaration of births among the Peulh. Based on interviews with 44 respondents obtained on the basis of saturation, the study notes that this phenomenon can be explained by the perceptions of the Fulani of civil status and the emergence of the Koranic school, which creates an environment hostile to modernism. Moreover, the lifestyle characterised by transhumance constitutes another explanatory logic, especially since the Fulani believe that the transhumant does not need administrative documents because nature does not belong to anyone.